Tingkat Stress pada Remaja Di Lapas Anak Blitar - Ariyanto, Eko April (Persona:Jurnal Psikologi Indonesia, 2016)
The purpose of this study was to determine the level of stress in adolescents who livein prisons Anak Blitar. The research subject is teenagers who are undergoing punishment inprisons Children Blitar number of 31 teens selected by random sampling. The data collectionstudy conducted by DSI Scale (Daily Stress Inventory) compiled by Brandey & Jones (1989),and self-report. The data were processed with descriptive analysis of the results show that 32,56% of adolescents in prisons Children experience stress levels are very high, 67.74% indicatesthat the category is quite high and there are no young people in prisons child who shows thelevel of stress in the normal category.Keywords : Stress, Adolescents, Prison of Child